Efeito de distúrbio causado pelo despejo de efluente orgânico sobre a comunidade de insetos aquáticos - ARAÚJO, Cecília Santiago do Carmo (2011)
Among several environmental impacts caused by human activities, the release of domestic and industrial effluents has been major disturbances that cause degradation of water quality in natural systems by altering their physical, chemical and biological features. For this reason, the aim of this work was to evaluate the effect of discharging organic waste from five Sewage Treatment Plants (STP) on abundance, richness and composition of aquatic insect fauna present in streams receiving sewage, in addition to test the hypotheses that i) disturbance caused by the discharge of effluents from STP alters the abundance of some groups of aquatic insects in the site downstream when compared to the upstream of site and ii) the taxonomic composition of the downstream impact of STPs is modified by the presence of resistant taxa.Thus, the sampling of aquatic insects and measures of some limnological variable was carried out during the drought of 2010, with the Surber sampler, 100m upstream and 100m downstream from the effluent discharge. Chironomidae and EPT larvaes (Ephemeroptera, Plecoptera and Trichoptera) were identified to genus. To test the hypothesis, a paired t test was performed with logarithmic data of total abundance, a paired t test with the richness of taxa identified at family and genus level. To evaluate the composition of the taxa sampled in two parts in relation to environmental variables were carried out two CCA separately, one with the taxa of Chironomids and one with the EPT. The results showed that abundances recorded downstream (μ = 4523.8 ± 2578.9) was higher than that recorded upstream (μ = 863.4 ± 508.4) on all STP. The results of paired t test using values of total abundance of taxa showed significant differences between upstream and downstream (paired t test: t = 4.21, d.f. = 4, p = 0.01), indicating the elimination of sensitive taxa and the increase abundance of dominant taxa, favored by the physical and chemical changes of water, such as Chironomus, resistant to high concentrations of organic debris. Both genera richness (paired t test: t = 0.791, d.f. = 4, p = 0.473) as the families (paired t test: t = 1.537, df = 4, p = 0.199) were not different in two sites, showing that this indicator is not the most appropriate in cases in which there is replacement of taxa.The ordinations produced by the CCAs were complementary, confirming the replacement of taxa between upstream and downstream, where larvaes like Farrodes, Tricorythodes, Alisotrichia and Mortoniella were favored by more oxygenated water. Thus, it was evident that the organic sewage discharge by STP modified the community structure of aquatic insects found in streams increasing the abundance, altering the dominance order and causing replacement of taxa between upstream and downstream